PARADOKS KEBIJAKAN PUSAT DALAM PENGEMBANGAN SARANA PENDIDIKAN ISLAM - Sugianto, Edi; Maharani, Sekar Puan; Azzahra, Nurul (Jurnal Manajemen Pendidikan, 2025)
This research aims to analyze the dynamics of central government policies in the development of Islamic education facilities and infrastructure and to uncover the paradox between established regulations and their implementation in the field. This research uses a qualitative approach with the library research method. Data were obtained from government policy documents, legislation, and relevant journal articles and scientific books related to education policy and the management of Islamic educational facilities and infrastructure. Data analysis was conducted descriptively-analytically through a conceptual meta-analysis approach to identify policy patterns, implementation trends, and their implications for Islamic educational institutions. The research results indicate that, normatively, the central government's policies regarding the development of Islamic education facilities and infrastructure are in line with the mandate of laws and regulations and National Education Standards. However, at the implementation level, policy paradoxes are still found, characterized by weak coordination between the central and regional governments in the context of regional autonomy. This condition often leaves madrasahs in a vacuum of responsibility, resulting in suboptimal fulfillment and management of facilities and infrastructure. The difficulties of digitizing learning, especially during the Covid-19 pandemic, have made the gaps in infrastructure and technological literacy in Islamic schools even more clear.